Byles on bills of exchange and cheques. - Elliott, Nicholas, 1945- (Sweet & Maxwell, 2002)
Provides a detailed narrative account of the law of bills of exchange, promissory notes, bank notes and cheques, arranged in order of topics covered by the Bills of Exchange Act 1882 and Cheques Act 1957. This survey traces the development of the law through recent legislation and case law.